[Readmission to an Adolescent Psychiatry Inpatient Unit: Readmission Rates and Risk Factors] - Mendes, P. (2017)
INTRODUCTION: Most mental disorders have a chronic evolution and therefore a certain amount of psychiatric readmissions are inevitable. Several studies indicate that over 25% of child and adolescent inpatients were readmitted within one year of discharge. Several risk factors for psychiatric readmissions have been reported in the literature, but the history of repeated readmissions is the most consistent risk factor. Our aim is to calculate the readmission rates at 30 days and 12 months after discharge and to identify associated risk factors. MATERIAL AND METHODS: The authors consulted the clinical files of patients admitted to the Inpatient Unit between 2010 and 2013, in order to calculate the readmission rates at 30 days and at 12 months. The demographic and clinical characteristics of the readmitted patients were analyzed and compared with a second group of patients with no hospital readmissions, in order to investigate possible predictors of readmission. RESULTS: A total of 445 patients were admitted to our inpatient unit between 2010 and 2013. Six adolescents were readmitted in a 30 days period (1.3%) and 52 were readmitted in a 12 month period after discharge (11.5%). Duration of the hospitalization and the previous number of mental health admissions were significant predictors of future hospital readmissions (p = 0.04 and p = 0.014). DISCUSSION: The low readmission rates may reflect the positive clinical and sociofamilial support being provided after discharge. CONCLUSION: Rehospitalisation is considered a fundamental target for intervention concerning prevention and intervention in mental healthcare. Thus, knowledge regarding their minimisation is crucial.